2021
DOI: 10.1039/d1cc00262g
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric catalytic [4+3] cycloaddition of ortho-quinone methides with oxiranes

Abstract: A chiral N,N′-dioxide/Tb(OTf)3 complex catalyzed diastereo- and enantioselective [4+3] cycloaddition of ortho-quinone methides with oxiranes has been described in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…Herein, we present the first example of a palladium-catalyzed intermolecular asymmetric dearomative annulation of phenols with VCPs to yield chiral spiro-[5,6] bicycles bearing an all-carbon quaternary center (Scheme c); such structural motifs are important components of many natural products and biologically active molecules (Figure ). Different from previous reports, the aromatic tetrahydrobenzo­[ b ]­oxepine skeleton from [4 + 3] annulation was not observed in this report. During the preparation of this manuscript, Miao reported a related work using Pd-catalyzed asymmetric [3 + 2] and [3 + 4] cycloadditions of a few separable o -QMs with oxindole-based spirovinylcyclopropanes, but the instability of ortho -quinone methides makes it difficult to enlarge reaction scopes and scales …”
contrasting
confidence: 99%
“…Herein, we present the first example of a palladium-catalyzed intermolecular asymmetric dearomative annulation of phenols with VCPs to yield chiral spiro-[5,6] bicycles bearing an all-carbon quaternary center (Scheme c); such structural motifs are important components of many natural products and biologically active molecules (Figure ). Different from previous reports, the aromatic tetrahydrobenzo­[ b ]­oxepine skeleton from [4 + 3] annulation was not observed in this report. During the preparation of this manuscript, Miao reported a related work using Pd-catalyzed asymmetric [3 + 2] and [3 + 4] cycloadditions of a few separable o -QMs with oxindole-based spirovinylcyclopropanes, but the instability of ortho -quinone methides makes it difficult to enlarge reaction scopes and scales …”
contrasting
confidence: 99%
“…ortho -Quinone methides ( o -QMs) have been widely used as versatile building blocks in the synthesis of important oxa-cyclic compounds. 13,14 We initiated our study by using 2-(1-alkynyl)-2-alken-1-one 1a and ortho -quinone methide 2a as the model substrates (Table 1). First, investigation of different reaction parameters, such as gold catalysts, chiral ligands and silver salts, showed that chiral phosphoramidite ligands and AgNTf 2 were beneficial for this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…9 For example, the asymmetric [4 + n ] ( n = 1, 2, 3) cyclization reactions of o -QMs that provide facile access to five-, six- or seven-membered rings have been well developed. 10 In contrast, o -QMs have scarcely been employed in higher-order cycloaddition to construct chiral eight-membered rings, 11 probably due to the disfavored ring strain and stereochemical control issue during the process.…”
Section: Introductionmentioning
confidence: 99%